2018
DOI: 10.5194/tc-12-2147-2018
|View full text |Cite
|
Sign up to set email alerts
|

Observations and modelling of algal growth on a snowpack in north-western Greenland

Abstract: Abstract. Snow algal bloom is a common phenomenon on melting snowpacks in polar and alpine regions and can substantially increase snow melt rates due to the effect of albedo reduction on the snow surface. In order to reproduce algal growth on the snow surface using a numerical model, temporal changes in snow algal abundance were investigated on the Qaanaaq Glacier in north-western Greenland from June to August 2014. Snow algae first appeared at the study sites in late June, which was approximately 94 h after a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(95 citation statements)
references
References 48 publications
9
86
0
Order By: Relevance
“…Mass concentrations of MD in surface snow at the study site during the observational period have been observed in previous studies (Onuma et al, 2018).…”
Section: Quantification Of Snow Impuritiessupporting
confidence: 61%
See 4 more Smart Citations
“…Mass concentrations of MD in surface snow at the study site during the observational period have been observed in previous studies (Onuma et al, 2018).…”
Section: Quantification Of Snow Impuritiessupporting
confidence: 61%
“…They consisted mostly of the spherical red cells of Cd. nivalis, and their mean diameter was 21.3 ± 2.3 µm (Onuma et al, 2018).…”
Section: Study Sites and Observation Methodsmentioning
confidence: 99%
See 3 more Smart Citations